Asuhan Keperawatan Pada Pasien CKD On HD dengan Penerapan Intervensi Latihan Fisik Range Of Motion (ROM) Terhadap Tingkat Fatigue - Muocharla Frisca; Aniska Indah Fari; Keristina Ajul (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
Background: Decreased kidney function which causes metabolic waste and fluids in the body to accumulate can disrupt the body's homeostatic balance and this is known as chronic kidney failure. One of the treatments that can be done is hemodialysis/dialysis. One of the side effects of hemodialysis is fatigue, this is because the kidneys cannot carry out their function of producing the hormone erythropoietin so the number of red blood cells is low. The physical exercises that can be done to overcome fatigue are range of motion exercises: Range of Motion (ROM). Objective: To analyze nursing care for CKD on HD patients by implementing Range of Motion (ROM) physical exercise interventions on fatigue levels. Method: The application of EBP is a case study using a pre-experimental method and a One group pretest-posttest design approach with a sample of 3 respondents, the instrument uses a questionnaire sheet. Range of Motion (ROM) intervention was carried out during the first 2 hours of intradialysis for 20 minutes. Results: After applying it for 3 times, there was a decrease in the level of fatigue in the three respondents can be concluded that there is a change in the level of fatigue before and after the Range of Motion (ROM) intervention. Suggestion: The results can provide motivation and a source of information for patients undergoing Hemodialysis who can apply Range of Motion (ROM) independently as an effort to reduce fatigue levels.